Taxonomic status of Rana nigromaculata mongolia and the validity of Pelophylax tenggerensis (Anura, Ranidae) - Zhou, Shengbo; He, Li; Ma, Siyu; Xu, Shujun; Zhai, Qiang; Guan, Ping; Wang, Hui; Shi, Jingsong (Zootaxa, 2022)
The Black-spotted Pond Frog, Pelophylax nigromaculatus, is widely distributed across mainland China, Korean Peninsula, and Japan. The taxonomic relationships among P. n. nigromaculatus, Rana nigromaculata mongolia (sensu P. n. mongolicus), and P. tenggerensis have long been ambiguous. Here we examine the topotype specimens of P. tenggerensis and R. n. mongolia, and provide phylogenic analyses based on four mitochondrial DNA sequences. The combined evidences from morphology and molecular phylogeny have shown the distinct specific-level of P. n. mongolicus that distant from P. nigromaculatus, while indicating the homogeneity between P. n. mongolicus and P. tenggerensis. Thus, we suggest elevating P. n. mongolicus as a full species Pelophylax mongolicus comb. nov., and place P. tenggerensis to be a secondary synonym of P. mongolicus comb. nov.